Rancang Bangun Aplikasi Umkm ABC Furnitur Berbasis Mobile - Muhamad Maulana Faisal; Marjuki Pilliang (Nindikayla Institute, 2025)
AdThe business world has changed due to advances in information and mobile technology. This is especially true for MSME businesses. As one of the UMKM that sells furniture, ABC Furniture has experienced a major impact from these developments. This study aims to improve the competitiveness of ABC Furniture UMKM by designing and building mobile-based applications using the Extreme Programming method to maximize the expanding market potential. Two problems found are suboptimal operational efficiency and obstacles in utilizing existing market potential. Therefore, the solution proposed by this study is the development of a phone application that can display complete products with images and descriptions, an online ordering system, electronic payment communication, and order status notifications. The application's user interface is made to be more user-friendly and responsive. It is possible that ABC Furniture UMKM can implement mobile applications to increase market reach, improve operational efficiency, and strengthen their digital presence in an increasingly connected business era. This expected solution can help UMKM in overcoming contemporary market challenges and make a positive contribution to the growth and aspirations of their businesses.